2001
DOI: 10.1002/tox.1048
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and purification of the zwitterions cylindrospermopsin and deoxycylindrospermopsin from Cylindrospermopsis raciborskii

Abstract: The hepatotoxin cylindrospermopsin (CYN) has been isolated from the cyanobacterium Cylindrospermopsis raciborskii (C. raci.). Efforts to study this toxin have been hampered by the time-consuming requirement to extract it from cultures of the organism. It is usually extracted from lyophilized cells collected from a laboratory culture. Our preliminary work suggested far more of the toxin is available in solution in the culture media than in the cells collected. We have therefore investigated the use of commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 9 publications
3
59
0
2
Order By: Relevance
“…At this stage, attention should be paid to the differences in the elution volume for methanol obtained in our work when compared with those from Norris et al (2001) and Metcalf et al (2002), where total recovery was obtained in about 8 mL, half the volume observed in the present study. An explanation to this different behavior may be found in the bed weight of the cartridges.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…At this stage, attention should be paid to the differences in the elution volume for methanol obtained in our work when compared with those from Norris et al (2001) and Metcalf et al (2002), where total recovery was obtained in about 8 mL, half the volume observed in the present study. An explanation to this different behavior may be found in the bed weight of the cartridges.…”
Section: Discussionmentioning
confidence: 68%
“…While quantification methods are well developed Törökné et al 2004), concentration and extraction of dissolved CYN from natural samples has not been widely developed or published. Norris et al (2001) completed a first approach toward an effective SPE method by selecting graphitized carbon as the most suitable compound when compared with a wide range of the most usual SPE sorbents. Also, in their work, the need for acidification of the solvents was established.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations